Understanding the inter-specific dynamics of two co-existing predators in the Tierra del Fuego Archipelago: The native southern river otter and the exotic American mink - Valenzuela, Alejandro Eduardo Jorge; Raya Rey, Andrea Nélida; Fasola, Laura; Schiavini, Adrian Carlos Miguel (Biological Invasions)
Knowledge about interactions between endangered native southern river otters (Lontra provocax) and introduced American mink (Neovison vison) is essential for effective management of both species. We evaluated competition for spatial and trophic niches between otter and mink in overlapping and non-overlapping areas, comparing distribution, habitat preference, diet and mink marking behavior. We surveyed otter and mink signs along 250 km of Beagle Channel coastline. Habitat suitability models were constructed based on species presence/absence and habitat characteristics, using generalized linear models. Feces were collected for diet analyses. Otters used forested coasts with 12°–32° shoreline slope and without human influence, and our evidence suggests they were not affected by mink presence. Mink preferred forested and shrubland coasts with 10°–28° shoreline slope. Neither human influence nor otter presence affected mink habitat occupation, but in the presence of otters, mink left fewer signs. Otters consumed more aquatic prey than mink, and mink modified their diet in the presence of otters, consuming more exotic small terrestrial mammals and less fish as well as shifting to smaller and shallower fish species that are less consumed by otters. Mink showed more plastic, generalist behavior than otters, being more tolerant of human presence, using more habitat types and having greater diet breadth. At the same time, otters apparently affect mink adversely and could help limit their invasion in sympatric areas. Conservation and recovery of otters, therefore, may produce a secondary benefit of simultaneously reducing the effect of mink, thereby providing an additional way to control this exotic predator’s population. Fil: Valenzuela, Alejandro Eduardo Jorge. Administración de Parques Nacionales. Delegación Regional Patagonia; Argentina. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Austral de Investigaciones Científicas; Argentina Fil: Raya Rey, Andrea Nélida. Consejo Nacional de ...